PENGARUH LATIHAN PENGANTAR SKILL DRIBBLING, CAPPING, FEINTING TERHADAP KECEPATAN DRIBBLING TIM SEKOLAH SEPAK BOLA WONER 2012 KELOMPOK USIA (KU) 13 TAHUN - Alim Adi Wangsa; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this study is that players lack the ability to dribble both in training sessions and in matches. During the training session in playing the game, there are still many players who lose the ball when dribbling past the opponent, the ball is far from the feet when dribbling and slowly changes the direction of the ball from one position to another when dribbling. The purpose of this study was to determine the effect of introductory training on dribbling, capping, feinting skills on the dribbling speed of the 2012 Woner Football School Team Age Group (KU) 13 years. The method used in this research is the experimental method. The research design carried out in this study was